Champions : John Ahearn - Donald Baechler - Jean-Michel Basquiat - James Brown - Ronnie Cutrone - Brett De Palma - Keith Haring - Futura 2000 - Tom Otterness - Kenny Scharf - Zadik Zadikian. (New York : Tony Shafrazi Gallery, 1983)
John Ahearn - Donald Baechler - Jean-Michel Basquiat - James Brown - Ronnie Cutrone - Brett De Palma - Keith Haring - Futura 2000 - Tom Otterness - Kenny Scharf - Zadik Zadikian
Champions : John Ahearn - Donald Baechler - Jean-Michel Basquiat - James Brown - Ronnie Cutrone - Brett De Palma - Keith Haring - Futura 2000 - Tom Otterness - Kenny Scharf - Zadik Zadikian, Tony Shafrazi Gallery, New York, 1983
boek